2005
DOI: 10.1002/ana.20633
|View full text |Cite
|
Sign up to set email alerts
|

A common pattern of persistent gene activation in human neocortical epileptic foci

Abstract: Epilepsy is a disease of recurrent seizures that can develop after a wide range of brain insults. Although surgical resection of focal regions of seizure onset can result in clinical improvement, the molecular mechanisms that produce and maintain focal hyperexcitability are not understood. Here, we demonstrate a regional, persistent induction of a common group of genes in human epileptic neocortex in 17 patients with neocortical epilepsy, regardless of the underlying pathology. This relatively small group of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
110
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 41 publications
3
110
0
Order By: Relevance
“…Upstream of CREB activation, several known signaling pathways are rapidly activated in response to neuronal activity (Kandel 2001; reviewed in West et al 2002), including CaMKinase IV, protein kinase A, and MAPK. We have recently observed a pattern of transcriptional activation in human brain regions where seizures start that strongly implicates sustained MAPK/CREB activation and downstream coding gene activations that could underlie layerspecific changes in synaptic architecture that makes these regions prone to seizures (Rakhade et al 2005;Barkmeier et al 2012;Beaumont et al 2012).Given that human lncRNA genes tend to be less wellconserved than protein-coding genes, and can give rise to unique transcripts not found in other species, we sought out a uniquely human system to examine activity-dependent gene expression for both coding and noncoding RNAs using a pairwise comparison of human cortical regions displaying variable degrees of epileptic activities. These brain regions were removed as part of surgical treatment for intractable seizures.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Upstream of CREB activation, several known signaling pathways are rapidly activated in response to neuronal activity (Kandel 2001; reviewed in West et al 2002), including CaMKinase IV, protein kinase A, and MAPK. We have recently observed a pattern of transcriptional activation in human brain regions where seizures start that strongly implicates sustained MAPK/CREB activation and downstream coding gene activations that could underlie layerspecific changes in synaptic architecture that makes these regions prone to seizures (Rakhade et al 2005;Barkmeier et al 2012;Beaumont et al 2012).Given that human lncRNA genes tend to be less wellconserved than protein-coding genes, and can give rise to unique transcripts not found in other species, we sought out a uniquely human system to examine activity-dependent gene expression for both coding and noncoding RNAs using a pairwise comparison of human cortical regions displaying variable degrees of epileptic activities. These brain regions were removed as part of surgical treatment for intractable seizures.…”
mentioning
confidence: 99%
“…Our human lncRNA gene catalog is mostly nonredundant with respect to other recently published human lncRNA collections ( Figure S2 in File S4). In contrast to our custom lncRNA array, current commercial microarray platforms do not adequately represent many genomically complex loci, including those encoding lncRNA genes and sense-antisense pairs (Orlov et al 2007;Jia et al 2010).Both platforms utilized a dye-flip (Kerr and Churchill 2001a) quadruplicate experimental design to obtain the most accurate statistical comparison of each pair of tissue samples from each patient (Yao et al 2004;Rakhade et al 2005;Beaumont et al 2012). Each within-patient sample pair was analyzed, using the same dye-flip quadruplicate strategy, for both the catalog coding (G4112A) and the custom lncRNA microarray.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This transcription factor has also been found to be upregulated in epileptic rats. In human focal epilepsies the transcription factors Egr-1, Egr-2 and c-fos have been found to be upregulated (Rakhade, Yao et al 2005). As a result of these findings, the GABRA4 promoter has emerged as our choice of promoter to deliver TREK-M in epileptic rats.…”
Section: Gabra4 Promotermentioning
confidence: 99%
“…Studies have also shown that in human focal epilepsy there is an increased expression of transcription factors Egr-1, Egr-2 and c-fos (Rakhade, Yao et al 2005). Human and rat GABRA4 have consensus binding sites for the Egr family (Rakhade, Yao et al 2005). Also we have used 542 bp fragment of GABRA4 promoter which is easier to package in an AAV packaging vector with size limit of 2.4 kb only.…”
Section: Gabra4 Promotermentioning
confidence: 99%